IMO Second Generation Intact Stability Criteria: General Overview and Focus on Operational Measures - Nicola Petacco; Paola Gualeni (Journal of Marine Science and Engineering, 2020)
At the beginning of 2020, after a long and demanding process, the Second Generation Intact Stability criteria (SGISc) have been finalized at the 7th session of the International Maritime Organization (IMO) sub-committee on Ship Design and Construction (SDC). At present, SGISc are not mandatory, nevertheless IMO endorses their application in order to assess their consistency and validity. It is envisaged that SGISc can support the design of safer ships, nevertheless such a rules framework might have an impact also on the ship operational aspects in a seaway. In fact, within the SGISc framework, Operational Measures have also been implemented providing guidance and limitations during navigation. After a comprehensive overview about SGISc vulnerability levels and direct stability assessment, this paper provides a specific insight into the methodological approach for the Operational Measures extensively addressed as a complementary action to ship design.